Case report: Molecular characterization of adult atypical teratoid rhabdoid tumor and review of the literature - Hernandez-Rovira, Miguel A.; Connor, Michelle; Osorio, Robert C.; Russler-Germain, Emilie; Schmidt, Robert; Johnson, Gabrielle W.; Silverstein, Julie; Dahiya, Sonika; Farrell, Nyssa Fox; Weiss, Mia C.; Zipfel, Gregory J.; Huang, Jiayi; et al. (Frontiers in Oncology, 2025)
Background and importanceAtypical teratoid rhabdoid tumors (ATRTs) are typically aggressive pediatric tumors with a median survival of 11 months. Due to the paucity of cases in adults, the clinical behavior of these pathologies is not well understood. Here we present the case of a 41-year-old female patient with postoperative hyperprogression of a sellar ATRT and provide a detailed description of the molecular composition of this tumor, the protocol used to treat this patient, and the ultimate outcome of this patient.Clinical presentationThe patient is a 41-year-old woman who presented with headaches and double vision. MRI revealed a sellar/suprasellar mass with involvement of bilateral cavernous sinuses. Following the quick symptom progression, resection of the tumor with exploration of the bilateral cavernous sinuses was performed, with a final pathologic diagnosis of ATRT-MYC, a known subtype of ATRT. The tumor recurred within 1 month of surgery, attaining a size equivalent to its preoperative state. Postoperatively, the patient received craniospinal radiation and adjuvant chemotherapy with an excellent response but had a recurrence of the tumor in the brainstem 1 year after her diagnosis and died 13 months after presentation.DiscussionSellar ATRT in adults is an exceedingly rare entity. The detailed description of our case highlights the aggressiveness of these tumors and the utility of postoperative chemotherapy and radiation, but also the inevitable progression of these tumors along the craniospinal axis.ConclusionSellar ATRTs should be considered in the differential diagnosis of a sellar/suprasellar mass, especially in women in their 40s. Emphasis should be placed on accurate diagnosis and quick postoperative recovery with early initiation of adjuvant radiation and chemotherapy.